Premature browning in cooked ground beef after modifying myoglobin - Hunt, Melvin C.; Warren, K.E.; Kropf, Donald H.; Hague, M.A.; Waldner, C.L.; Stroda, Sally L.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Some ground beef patties developed an internal, brown cooked color and looked well-done at temperatures as low as 131 ̊F, whereas normal patties were re d to pink. The premature brown color was not relate d to percent fat; patty compaction; animal source and maturity; pH (5.5 to 5.8); or concentrations of raw patty heme and nonhemeiron, myoglobin, and total pigment. Because oxidation-reduction potential and total reducing activities were higher (P<.05) and TBA numbers were lower (P<.05) in normal than prematurely brown patties, the brown color is apparently related to greater patty oxidation.
Keywords: Beef; Ground beef; Cooked color; Oxidation; Reduction; Food safety